(untitled) (REMUNOM, 2025)
Abstract This study analyzed the influence of pharmaceutical marketing on self-medication practices, focusing on the advertising of over-the-counter drugs and its impact on public health. The objective was to understand how marketing strategies encourage the indiscriminate consumption of pharmaceuticals, leading to risks such as intoxication, chemical dependence, and drug resistance. The research was based on a bibliographic review of scientific articles and recent academic studies, evaluating the relationship between pharmaceutical advertising and its influence on the sale of medications without medical prescription. The results indicated that persuasive advertising campaigns, broadcasted through digital, television, and print media, emphasize the benefits of medications while downplaying their risks, creating a false sense of security. Furthermore, the ease of access to over-the-counter drugs reinforces the habit of self-medication, often without proper professional guidance. It is concluded that the regulation of drug advertising should be improved to ensure more balanced and transparent information, combined with strengthening the role of pharmacists as key agents in promoting the rational use of medicines. Keywords: Self-medication; Pharmaceutical Marketing; Drug Advertising.